2006
DOI: 10.1242/dev.02339
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog regulates Gli activator and repressor functions with spatial and temporal precision in the mid/hindbrain region

Abstract: The midbrain and anterior hindbrain offer an ideal system in which to study the coordination of tissue growth and patterning in three dimensions. Two organizers that control anteroposterior (AP) and dorsoventral (DV) development are known, and the regulation of AP patterning by Fgf8 has been studied in detail. Much less is known about the mechanisms that control mid/hindbrain development along the DV axis. Using a conditional mutagenesis approach, we have determined how the ventrally expressed morphogen sonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
222
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(243 citation statements)
references
References 45 publications
(74 reference statements)
16
222
3
2
Order By: Relevance
“…Interestingly, Shh is required during development for the specification of several neuronal populations, including DA SNpc. Shh is embryonically secreted from the ventral floor and basal plates, and the absence of Shh leads to a reduction in the number of DA SNpc (Blaess, Corrales, & Joyner, 2006). The described expression of Shh in DA SNpc (Gonzalez‐Reyes et al, 2012) combined with our results suggest a plausible role for Shh in the specification of striatal interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Shh is required during development for the specification of several neuronal populations, including DA SNpc. Shh is embryonically secreted from the ventral floor and basal plates, and the absence of Shh leads to a reduction in the number of DA SNpc (Blaess, Corrales, & Joyner, 2006). The described expression of Shh in DA SNpc (Gonzalez‐Reyes et al, 2012) combined with our results suggest a plausible role for Shh in the specification of striatal interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…278 Among multiple other roles, SHH is important for normal embryonic patterning, including the development of midbrain and hindbrain structures. 279,280 One study has suggested that the administration of SHH can partially attenuate the neurotoxic effects of valproic acid on early serotonergic neuronal development. 252 SHH may produce effects through the PI3K pathway, 281 which is also important for normal brain development.…”
Section: Genes Responsive To Environmental Factorsmentioning
confidence: 99%
“…Recent advances in stem cell technology and breakthroughs in identifying the transcriptional cascades involved in specifying midbrain dopaminergic neurons have renewed interest in understanding how overall midbrain patterning is accomplished (Bayly et al, 2007;Agarwala et al, 2001;Simeone, 2005;Blaess et al, 2006). Two major signaling centers, the midbrain-hindbrain boundary (MHB), and the floor plate have been implicated in establishing midbrain pattern (Marti et al, 1995;Joyner, 1996;Blaess et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in stem cell technology and breakthroughs in identifying the transcriptional cascades involved in specifying midbrain dopaminergic neurons have renewed interest in understanding how overall midbrain patterning is accomplished (Bayly et al, 2007;Agarwala et al, 2001;Simeone, 2005;Blaess et al, 2006). Two major signaling centers, the midbrain-hindbrain boundary (MHB), and the floor plate have been implicated in establishing midbrain pattern (Marti et al, 1995;Joyner, 1996;Blaess et al, 2006). The midbrain/rostral floor plate (rFP) is a source of the signaling molecule Sonic Hedgehog (SHH), whose role in specifying ventral neural cell-fates is well established (Chiang et al, 1996;Jessell, 2000;Agarwala et al, 2001;Fedtsova and Turner, 2001;Blaess et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation